Papel da terapia fotodinâmica antimicrobiana adjuvante ao tratamento periodontal sob parâmetros de estresse oxidativo plasmático e comportamento vascular - Barin, Luisa Machado (2015)
The aim of this study was to evaluate the effects of methylene blue (MB) photosensitizer (PS) solubilized in ethanol in antimicrobial photodynamic therapy (aPDT) as an adjuvant periodontal treatment, at oxidative stress (OS) parameters and vascular behavior in rat model. Besides, investigate greater involvement of angiogenesis at the destruction or healing stages of periodontal disease (PD). One hundred and twenty male adult Wistar rats were divided randomly into five groups. The control groups were negative control (NC) (no PD, n=15) and positive control (PC) (with PD, without any treatment, n=15). The other groups had PD and underwent different types of treatment, such as scaling and root planing (SRP) and irrigation with 1mL of saline solution (SRP, n=30); SRP and aPDT with MB solubilized in water (aPDT I, n=30); SRP and aPDT with MB containing ethanol (aPDT II, n=30). The PD was induced via the installation of a ligature around the mandibular right first molar. After 7 days, the ligature was removed and animals received treatment. At 7, 15 and 30 days, rats were euthanized and the gingival tissue surrounding the induction area was removed for histomorphometric analysis of the number and diameter of blood vessels by staining with hematoxylin and eosin (H&E). The collected blood was centrifuged and the plasma was used to determine lipid peroxidation by quantifying thiobarbituric acid reactive substances (TBARS), vitamin C (VIT C) and glutathione reduced (GSH) levels. The oxidative status showed higher TBARS levels in PC group in 7, 15 and 30 days, and indicated a protective influence of aPDT II on plasma observed from lower lipid peroxidation. GSH levels were consumed in PC, aPDT I and aPDT II groups throughout the experiment. Furthermore, aPDT II also increased antioxidant defenses in plasma: i) higher levels of GSH, and ii) increased levels of VIT C. Interestingly, the VIT C plasmatic levels were restored in the aPDT II group in the 30th experimental day. Histomorphometric findings in 7 days showed that treated groups (SRP, aPDT I and aPDT II) showed higher number of blood vessels, and the aPDT II group showed the highest values among them. From these results, aPDT modifies PD course, reducing oxidative systemic damage and stimulating the antioxidant defense system, thus protecting the areas closely affected by PD in rats. Moreover, was observed a relationship between increased expression of angiogenesis and repair stage of the PD. In summary, we suggest that the aPDT with MB solubilized in ethanol provides better therapeutic responses in periodontal treatment.